Money on the move : the modern international capital market - Mendelsohn, Stefan (New York : McGraw-Hill, 1980)
The book is divided into three parts. Part one x-rays the markets roles and origins; part two looked at the offshore markets Eurocredits and Eurobonds; while part three considers foreign bond markets and financial centers.
Includes index.
Bibliography: p. 279-280.
rua15/5/2017
Loans
Keywords: Capital market; Capital movements; Euro-bond market; Euro-dollar market; Foreign exchange market